Characterization of smallest active monomeric lipase from novel rhizopus strain: application in transesterification - Kantak, Jayshree B.; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2012)
An extracellular lipase-producing fungus was isolated from oil-rich soil. This fungus belongs to the genus Rhizopus and clades with Rhizopus oryzae. Lipase was purified to homogeneity from this novel fungal source using ammonium sulphate precipitation followed by Q-Sepharose chromatography. The extracellular lipase was purified 8.6-fold, and enzymatic properties were studied. The molecular mass of the purified enzyme was estimated to be 17 kD by sodium dodecyl sulphate-polyacrylamide gel electrophoresis and 16.25 kD by matrix-assisted laser desorption ionization/time-of-flight analysis. The native molecular mass was estimated to be 17.5 kD by gel filtration, indicating the protein to be monomer. The optimum pH and temperature for the enzyme catalysis were 7.0 A degrees C and 40 A degrees C, respectively. Enzyme was stable in pH range 6.0-7.0 and retains 95-100% activity when incubated at 50 A degrees C for 1 h. The pI of the purified lipase was 4.2. Enzyme was stable in the organic solvents such as ethanol, hexane and methanol for 2 h. Purified enzyme was used for transesterification of oleic acid in the presence of ethanol for production of oleic acid ethyl ester with a conversion efficiency of 66% after 24 h at 30 A degrees C.
Keywords: Lipase; Low molecular weight; Purification; Rhizopus; transesterification